A modular approach for organizing dimeric coiled coils on peptoid oligomer scaffolds. Issue 12 (11th March 2020) - Jiang, Linhai; Kirshenbaum, Kent
Abstract : A peptoid oligomer macrocycle can be used as a scaffold for templating a dimeric coiled coil peptide assembly, substantially increasing its thermal stability. Abstract : We report a general approach to promote the folding of synthetic oligopeptides capable of forming homodimeric coiled coil assemblies. By pre-organizing the peptides on macrocyclic oligomer scaffolds, the stability of the coiled coils is enhanced with an observed increase in the melting temperature of 30 °C to 40 °C. Molecular dynamics simulations substantiate the hypothesis that the enhanced stability is established by constraining motion at the peptide termini and by pre-organizing intramolecular helix–helix contacts. We demonstrate the modularity of this approach by using a family of peptoid scaffolds to promote the folding of a dimeric coiled coil. Importantly, this strategy for templating coiled coils allows preservation of native amino acid sequences. Comparing a macrocyclic peptoid scaffold to its linear counterparts indicates that both types of assemblies are effective for organizing stable coiled coils. These results will guide future designs of coiled coil peptides for biomedical applications and as building blocks for more complex supramolecular assemblies.